Interaction Communication of Work System Adjustment at TVRI North Sulawesi Station - Wulur, Debby Ribkah; Masengi, Evi Elvira; Langkai, Jeane E. (Technium Social Sciences Journal, 2023)
This study aims 1) to find out, analyze and interpret the interaction communication of the adjustment of the new work system at TVRI North Sulawesi Station; 2) to find out, analyze and interpret the factors that influence the interaction communication of the adjustment of the new work system at TVRI North Sulawesi Station. The research method is a qualitative research method using a purposive side. Data collection techniques were interviews, documentation studies and observations conducted at the North Sulawesi TVRI Station Office. The results of the study show that the new work system, namely the Electronic-Based Government System (SPBE), has not been implemented smoothly. This new system actually caused problems at the TVRI North Sulawesi Station office, namely constraints and limitations on equipment and staff. The strategy used to overcome this problem is to build communication-based on motivation towards organizational targets, build synergy and create horizontal communication between employees through the right media under the encouragement and direction of the leadership in order to mobilize all existing potential.